A aplicabilidade da guarda compartilhada: o entendimento de promotores e juízes - Christofari, Gabriela Clerici (2019)
Joint custody was introduced in the Brazilian juridical scene in 2008, as a possibility for separated fathers and mothers to be able to keep their coexistence with their children. More recently, it was reaffirmed in the legal context through Law No. 13058, in 2014. Thus, it is understood that it is linked to the commitment to family ties, so that parenting can continue to be exercised. In view of the foregoing, the research that originates the present dissertation had the objective of know the understanding of Law operators – promoters and judges - about the applicability of joint custody. In this perspective, the study had a qualitative and exploratory character, being based epistemologically in the Complexity Paradigm. As a tool for data collection, the semi-structured interview was used. The data were analyzed through thematic content analysis. The results were presented through two scientific papers. The first paper was devoted to discuss the main understandings of the Law operators on joint custody, contextualizing also how custody is perceived by these professionals. In addition, the interdisciplinary work was pointed out by the participants as fundamental to the best applicability of the joint guard. Already, the second paper pointed out some issues perceived by the Law operators as obstacles to the use of joint custody. Among the aspects pointed out, the difficulties related to the supremacy of mothers in the care of their children stand out; the conflicts between the former couple; the confusions regarding the guard and the age of the children, among others. The study allowed to identify important changes, however, it is necessary to extend the discussions regarding joint custody, with a view to overcoming those aspects that still inhibit its greater use. Considering that the study had as participants legal operators, who are directly involved with the subject, it is understood that research constitutes an important contribution to the issue, expanding the spectrum of discussions in an interdisciplinary scope.